2021
DOI: 10.3389/fpsyt.2021.784131
|View full text |Cite
|
Sign up to set email alerts
|

Physician's Burnout and the COVID-19 Pandemic—A Nationwide Cross-Sectional Study in Austria

Abstract: Background: The current study assesses the prevalence of burnout and psychological distress among general practitioners and physicians of various specialities, who are not working in a hospital, during the COVID-19 pandemic. Additionally in this context, contributing factors are registered.Materials and Methods: Burnout and psychological distress were assessed with the Copenhagen Burnout Inventory (CBI) and the Brief Symptom Inventory (BSI-18). A newly developed self-reporting questionnaire was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Physicians experienced ever-increasing pressure in their daily lives, particularly at their work 41 43 . This upsurge was reported in some studies conducted worldwide 44 , 45 . Similar to other countries, Lebanon experienced many challenges imposed by the COVID-19 pandemic on its healthcare system which was already in a fragile state even before the pandemic 46 , the economic collapse 47 , and the Beirut blasting 48 .…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Physicians experienced ever-increasing pressure in their daily lives, particularly at their work 41 43 . This upsurge was reported in some studies conducted worldwide 44 , 45 . Similar to other countries, Lebanon experienced many challenges imposed by the COVID-19 pandemic on its healthcare system which was already in a fragile state even before the pandemic 46 , the economic collapse 47 , and the Beirut blasting 48 .…”
Section: Introductionmentioning
confidence: 59%
“…For example, a study reported that 45.8% of US physicians had experienced burnout 29 . Another study conducted among Austrian physicians showed a substantial increase of 30% in burnout rates during the pandemic compared to other studies conducted before the COVID-19 outbreak 7 , 8 , 45 .…”
Section: Discussionmentioning
confidence: 80%
“…By 2019, burnout in FDs had already been reported as worryingly common worldwide (Kay, 2012;Kings Fund, 2016;Shanafelt et al, 2019), in what was described as a "global crisis" for all doctors (Lancet editorial, 2019, p.93). Covid-19 struck later that year, and the challenges brought by being on the pandemic frontline have added greatly to the already high demands on the medical profession (Amanullah and Shankar, 2020;Kurzthaler et al, 2021). The mental health of FDs has been affected for the worse (Lasalvia et al, 2022), with concerns (Best, 2021;Iacobucci, 2021) and research evidence (Lum et al, 2021;Seda-Gombau et al, 2021) that FD burnout is becoming an even greater problem.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 , 15 , 16 The CBI has been applied extensively to physicians. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Despite widespread international use in measuring burnout among physicians, the CBI has been used infrequently to measure burnout among emergency physicians in the United States. 37 , 38 …”
Section: Introductionmentioning
confidence: 99%
“…The CBI has been used to assess varied types of health care personnel in several countries, amassing substantial validity evidence 13–16 . The CBI has been applied extensively to physicians 17–36 . Despite widespread international use in measuring burnout among physicians, the CBI has been used infrequently to measure burnout among emergency physicians in the United States 37–38 …”
Section: Introductionmentioning
confidence: 99%